Characterization of Macroporous Polycaprolactone/Silk Fibroin/Gelatin/Ascorbic Acid Composite Scaffolds and In Vivo Results in a Rabbit Model for Meniscus Cartilage Repair - Abpeikar, Zahra; Moradi, Lida; Javdani, Moosa; Kargozar, Saeid; Soleimannejad, Mostafa; Hasanzadeh, Elham; Mirzaei, Seyed Abbas; Asadpour, Shiva (Cartilage, 2021)
Meniscus injuries in the inner avascular zone have weak intrinsic self-healing capacity and often progress to osteoarthritis. This study focused on evaluating the effects of polycaprolactone/silk fibroin/gelatin/ascorbic acid (PCL/SF/Gel/AA) composite scaffolds seeded with adipose-derived mesenchymal stem cells (ASCs), in the meniscus repair. To this end, composite scaffolds were cross-linked using -hydroxysuccinimide and 1-ethyl-3-(3-dimethyl-aminopropyl)-1-carbodiimide hydrochloride. Scaffolds were then characterized by scanning electron microscope, mechanical tests, total antioxidant capacity, swelling, and toxicity tests. The PCL/SF/Gel/AA scaffolds exhibited suitable mechanical properties. Furthermore, vitamin C rendered them the highest antioxidant capacity. The PCL/SF/Gel/AA scaffolds also showed good biocompatibility and proliferation for chondrocytes. Moreover, the PCL/SF/Gel/AA scaffold seeded with allogeneic ASCs was engrafted in New Zealand rabbits who underwent unilateral punch defect in the medial meniscus of the right knee. After 2 months postimplantation, macroscopic and histologic studies for new meniscus cartilage were performed. Our results indicated that the PCL/SF/Gel/AA composite scaffolds seeded with allogeneic ASCs could successfully improve meniscus healing in damaged rabbits.